Voltage sag analysis and determination of the source of disturbance in industrial sector - Abdul Rasid, Faralyna Aisyah (2014)
Power quality analysis has become one of the main objective of study in electric power systems. Voltage sag is a phenomena where voltage decrease to 90% to 10% of the rated voltage, with a typical duration of 0.5 to 30 cycle. The purpose of this study is to analyze the voltage sag events in order to identify the source and the cause of voltage sag. Voltage sag is a power quality problem that seldom occurred, but once it occur, it will cause severe problems, such as industrial processes malfunction, producing great economic losses and reduce the power quality. To improve power quality, it is important to identify the source of disturbance. The analysis performed by using the data of voltage sag event shows that the major source of the voltage sag is because of the external factor, while the cause of the voltage sag are mainly by the short circuit. The mitigation technique shall be propose along the analysis, because the effect of the voltage sag can be reduce when applying the mitigation technique such as by using an Uninterruptable Power Supply (UPS) and Voltage Stabilizer at both utility and customer side.